The effect of teaching using the EDGA model on the acquisition of chemical concepts among first-year middle school students (Journal of the College of Basic Education, 2025)
This study aims to investigate the effect of teaching using the EDJA model on acquiring chemical concepts among first-year intermediate students. Based on the research objective, the null hypothesis was formulated stating that there is no statistically significant difference at the 0.05 level between the mean scores of the experimental group students taught using the EDJA model and the control group students taught by the traditional method in the chemical concepts acquisition test prepared specifically for this study.The study employed an experimental method with a quasi-experimental design for two equivalent groups. The researcher randomly selected one school and divided the students into two groups: an experimental group of 36 students and a control group of 35 students, making the total sample size 71 students. The two groups were statistically matched on the following variables: chronological age, Raven’s intelligence test, mid-year grades, and prior knowledge test The researcher determined the study content from selected units of the first-year intermediate chemistry curriculum and formulated behavioral objectives representing the first three cognitive levels according to Bloom’s taxonomy. The research instrument was an objective multiple-choice test designed according to a precise specification table to verify the acquisition of chemical concepts. The test’s validity and reliability were confirmed, with a suitable reliability coefficient measured by the Kuder-Richardson 20 formula.Appropriate statistical methods were used to analyze the data, and the results showed that the experimental group students outperformed the control group in acquiring chemical concepts.